Peran Komunikasi Interpersonal dalam Membentuk Persepsi Generasi Muda Terhadap Masa Depan Pertanian Indonesia: The Role of Interpersonal Communication in Shaping Young Generations' Perceptions of the Future of Indonesian Agriculture - Prastiwi, Chintamy Rizky; Rozaki, Zuhud; Wulandari, Retno; Azzahra, Isni (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
This research addresses the role that interpersonal communication plays in shaping young people's perceptions of the future of agriculture in Indonesia. Through a qualitative approach, we analyze communicative interactions between the younger generation and agricultural stakeholders. The results show that interpersonal communication plays a crucial role in shaping young people's views on the potential and challenges of the agricultural sector. Factors such as education, first-hand experience, and social media influence how these perceptions develop. The implications of these findings provide insight into communication strategies that can be used to inspire and engage the younger generation in advancing the future of Indonesian agriculture.